Randomised controlled trial of tailored support to increase physical activity and reduce smoking in smokers not immediately ready to quit: protocol for the Trial of physical Activity-assisted Reduction of Smoking (TARS) Study - Taylor, A; Thompson, TP; Ussher, M; Aveyard, P; Murray, RL; Harris, T; Creanor, S; Green, C; Streeter, AJ; Chynoweth, J; Ingram, W; Greaves, CJ; et al. (BMJ, 2020)
INTRODUCTION: Smoking reduction can lead to increased success in quitting. This study aims to determine if a client-focused motivational support package for smoking reduction (and quitting) and increasing (or otherwise using) physical activity (PA) can help smokers who do not wish to quit immediately to reduce the amount they smoke, and ultimately quit. This paper reports the study design and methods.